Inactivated Whole-virus Vaccine Triggers Low Response Against SARS-CoV-2 Infection Among Renal Transplant Patients: Prospective Phase 4 Study Results - Medina-Pestana, Jose; Covas, Dimas Tadeu; Viana, Laila Almeida; Dreige, Yasmim Cardoso; Nakamura, Monica Rika; Lucena, Elizabeth Franca; Requiao-Moura, Lucio R.; Branco Fortaleza, Carlos Magno Castelo [UNESP]; Foresto, Renato Demarchi; Tedesco-Silva, Helio; Cristelli, Marina Pontello (Lippincott Williams & Wilkins, 2022)
Background. Anti-severe acute respiratory syndrome coronavirus 2 mRNA vaccines elicit lower humoral responses in solid-organ transplant recipients. This is the first prospective trial investigating the effect of an inactivated whole-virion vaccine in kidney transplant recipients. Methods. Prospective, single-center, phase 4, interventional study. Kidney transplant recipients aged 30-69 y with >30 d of transplantation received two 3 mu g intramuscular doses of CoronaVac 28 d apart and are being followed for 6 mo. Primary outcomes: (1) reactogenicity after first dose; (2) antibody responses 28 d after each dose; and (3) incidence/severity of confirmed coronavirus disease 2019 (COVID-19) and 28-d lethality rate. For this analysis, clinical effectiveness was assessed for 3 mo, starting 15 d after the second dose, and compared with 3-mo period before vaccination. Results. Of the 3371 individuals who received the first dose, 99% completed vaccination schedule. Mild/local adverse reactions were reported by 33% of the patients. In the immunogenicity cohort (n = 942), the proportion of patients with IgG antibodies to severe acute respiratory syndrome coronavirus 2 increased from 15.2% after first dose to 43% after second dose. Increase in antibody values after second dose was associated with higher proportion of patients with detected neutralizing antibodies. A significant reduction in the incidence of COVID-19 was observed (6.4% versus 4.2%; P < 0.0001), although the 28-d lethality rate remained unchanged (25% versus 22%; P = 0.534). In 45 patients from the immunogenicity cohort who developed COVID-19, all the 6 deaths occurred among those without antibody response (n = 22; 49%). Conclusions. CoronaVac vaccine was associated with low reactogenicity, low immunogenicity but reduced incidence of COVID-19 among kidney transplant recipients. The lack of reduction in lethality rates is perhaps associated with the low percentage of patients developing humoral response after the second dose.